FREQUENCY OF CANINE RHABDOMYOSARCOMA IN THE HISTOPATHOLOGICAL VETERINARY LABORATORY OF SAN MARCOS UNIVERSITY (PERIOD 2000-2008) - Inga E., Edwin (2013)
The purpose of this study was to determine the frequency of canine rhabdomyosarcoma based on its histopathological classification, that were diagnosed in the histopathology laboratory of the Veterinary Faculty of San Marcos University, Lima, Peru in the period of January 2000 to December 2008. A total of 63 cases of canine rhabdomyosarcoma were diagnosed out of 1125 canine neoplasic tumors (5.6 ± 1.3%). Among this, only 47 cases were possible to classify where 27 cases (57.4%) corresponded to embryonal rhabdomyosarcoma, 19 (40.4%) to alveolar rhabdomyosarcoma, and one case (2.1%) to pleomorphic rhabdomyosarcoma. The most frequent region of the body affected by the embryonal type was the head and neck, where 6 to 10 year-old animals were the most affected.